Variations In Interactive Media Development To Improve Mastery Of Arabic Vocabulary/ Variasi Pengembangan Media Interaktif Untuk ‎Peningkatan Penguasaan Kosakata Bahasa Arab - As'ad, Muchamad Kharis; Nadzifah, Izzun; Rosyada, Amrina; Utami, Resgi Widati Tria Lis (Ijaz Arabi Journal of Arabic Learning, 2023)
This study aims to determine the feasibility of the game "Gudang Kata'' and to determine the increase in students' vocabulary mastery towards the use of this game in learning Arabic. This research is the R&D model research with six stages, namely potentials and problems, data collection, product design, product revision, design validation, and product trials. This product was reviewed by supervising lecturers, material experts, and media experts and responded to by 30 Classes. Product quality results are determined by calculating the average score of the quantitative data and then describing the qualitative data from the questionnaire results. As for the test of increasing students' vocabulary mastery, it is obtained from the results of the pretest and posttest and gains normality. The results of this development research game, "Gudang Kata," received a percentage from material experts for the suitability of the material, namely 100% in the "Very Good" category. According to media experts, the quality of the media obtained a percentage of 88.57% in the "Very Good" category. At the same time, the results of the responses of 30 students got a rate of 85.19% in the "Very Good" class. Then, the results of the analysis test for increasing students' Arabic vocabulary mastery increased by 0.7 in the "High'' category based on the acquisition of an average pretest score of 86.33 and an average posttest of 96.00.